(untitled) (Revista do CAAP, 2024)
Fruto de movimentos pós-II Guerra Mundial, o sistema interamericano de proteção aos direitos humanos está consagrado na Convenção Americana de Direitos Humanos, que possui dois principais órgãos para monitorar o respeito a esses direitos: a Comissão Interamericana de Direitos Humanos e a Corte Interamericana de Direitos Humanos. A primeira recebe denúncias de indivíduos e ONGs, conduz uma investigação junto ao Estado sobre o respeito às normas da Convenção e emite recomendações a fim de interromper a violação. A segunda atua quando essas recomendações não surtem efeito e julga o caso, podendo ordenar reparações à vítima. O artigo levanta informações para mostrar que, por meio desses órgãos, o sistema interamericano é efetivo frente a seus objetivos, mas sofre constrições. Analisa-se também como estas decisões impactam o Direito dos países latino-americanos. Sem pretensão de esgotar o assunto, instiga-se o leitor a se interessar pelo sistema continental de proteção aos direitos humanos. PALAVRAS-CHAVE: COMISSÃO INTERAMERICANA DE DIREITOS HUMANOS- CORTE INTERAMERICANA DE DIREITOS HUMANOS- DIREITOS HUMANOS- EFETIVIDADE – AMERICA LATINA. AMERICAN CONVENTION ON HUMAN RIGHTS: OPERATION AND EFFECTIVENESS OF THE MECHANISM OF PROTECTION OF HUMAN RIGHTS IN LATIN AMERICA Abstract: Resulting from post II World War movements, the interamerican system of human rights protection is ruled by the 1969 American Convention on Human Rights, which has two main bodies: the Interamerican Human Rights Commission and an Interamerican Court. The first is where individuals and NGOs can file suits against States, which will be then subject to an investigation and may be targeted by Commission recommendations in order to interrupt human rights violations. If these recommendations are ineffective, the Court analyses the case and may order reparations to the victim. The article raises information to demonstrate that, through theses organs, the interamerican system is effective in view of its objectives, though suffering constrictions. It also analyses the way in which these decisions impact member-countries internal law. Not expecting to end the subject, it intends to call the reader’s interest to the continental system of human rights protection. KEY-WORDS: INTERAMERICAN COMMISSION ON HUMAN RIGHTS- INTERAMERICAN COURT OF HUMAN RIGHTS – HUMAN RIGHTS- EFFECTIVENESS – LATIN AMERICA.